Analisis efisiensi dan skala ekonomi pada industri bumbu masak dan penyedap masakan di Indonesia - Putri Devintha S.B.; Imam Asngari; Suhel Suhel (Jurnal Ekonomi Pembangunan, 2018)
The purpose of this study is to determine technical efficiency, alocative/price efficiency and economies efficiency using production factors, and to know about economies of scale of seasoning and flavoring Industry in Indonesia. The data used in this research were secondary data with five digit ISIC (10772) using panel data and for the analytical techniques used in this study include multiple linear regression analysis as production function with stochastic production frontier approach. The result shows that labor production function has positive but insignificant impact on the production, while capital and material has positive and significant impact on the production. The value of technical efficiency is 0,7796 or 77,96% shows that the used of production factors is inefficient technically, the value of alocative/price efficiency is 1,7703 that is mean inefficient, the value of economies efficiency is 1,3801 7703 means that economies efficiency has not achieved the standard yet, and economies of scale is about 1,0203, means that the economies of scale is always increase or commonly known as incresing return to scale but, the value of economies of scale is equal to one, so that the economies of scale can be known as constant return to scale